2020
DOI: 10.1017/s1368980020002359
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and enablers of breast-feeding protection and support after the 2017 earthquakes in Mexico

Abstract: Objective: To study the barriers and enablers of breast-feeding protection and support after the 2017 earthquakes in Mexico. Design: A qualitative study using a phenomenological approach to analyse data collected from in-depth interviews, virtual ethnography and documentary analysis of newspapers. Setting: Data were collected after the September 2017 earthquakes in Mexico (from 8 September 2017 to 15 May 2018). Participants: The participants included k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 11 publications
(13 reference statements)
0
4
0
Order By: Relevance
“…This finding is consistent with findings from studies in other regions during the same period, which show that BMS companies are capitalizing on fear of breastfeeding during the pandemic to market their products [ 59 ]. Such strategies to promote and distribute BMS during emergencies such as earthquakes [ 60 , 61 ] and tsunamis [ 62 ] have been documented internationally [ 63 ]. Together, this evidence highlights that governments and international organizations need to step in to regulate BMS donations and guard mothers and infants against unnecessary promotion and distribution of BMS, which often reaches the most vulnerable populations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is consistent with findings from studies in other regions during the same period, which show that BMS companies are capitalizing on fear of breastfeeding during the pandemic to market their products [ 59 ]. Such strategies to promote and distribute BMS during emergencies such as earthquakes [ 60 , 61 ] and tsunamis [ 62 ] have been documented internationally [ 63 ]. Together, this evidence highlights that governments and international organizations need to step in to regulate BMS donations and guard mothers and infants against unnecessary promotion and distribution of BMS, which often reaches the most vulnerable populations.…”
Section: Discussionmentioning
confidence: 99%
“…For example, while the Mexican Government published clear guidelines that adhered to WHO recommendations, there were no targeted communication efforts to disseminate the key practices through traditional media platforms, hence, limiting the implementation at the clinical level. Finally, as highlighted in prior studies during crises and emergencies [ 60 ], governments need to have clearer protocols on how to enforce and monitor the protection and support of breastfeeding when such events arise.…”
Section: Discussionmentioning
confidence: 99%
“…Our study supports a protective effect of breastfeeding on the infant gut microbiome, specifically during a natural disaster. Since breastfeeding practices are largely impacted by inadequate disaster responses and subsequent barriers and challenges that mothers face during disasters, further studies and interventions are needed to understand, protect, and support breastfeeding during natural disasters ( 80 , 81 ). A previous study reported that gut microbial alterations in infants exposed to prenatal depression were dependent on breastfeeding, although alterations in infant gut immunity, such as impaired secretory IgA levels, were universal and independent of the feeding type ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…Such strategies to promote and distribute BMS during fragile circumstances such as earthquakes (47,48) and tsunamis (49), have been documented internationally (50). Prior evidence highlights that governments and international organizations need to step in to regulate such donations and guard mothers and infants from unnecessary promotion and distribution of BMS that usually reaches the most vulnerable.…”
Section: Discussionmentioning
confidence: 99%